Sistem Monitoring Data pada Smart Agriculture System Menggunakan Wireless Multisensor Berbasis IoT - Givy Devira Ramady; Rahmad Hidayat; Syafruddin R; Andrew Ghea Mahardika; Reza Rahman Hakim (Prosiding Seminar Nasional Teknoka, 2019)
The development of technology in the modernization era now allows us to do work more easily, quickly, efficiently and have high productivity. One example of this development is in agriculture. The concept of developing agriculture that is being developed at this time is the concept of intelligent agriculture, or more commonly known as smart farming or the Smart Agriculture System. This concept refers to the application of Information and Communication Technology (ICT) in agriculture. The main purpose of applying the technology is to increase yield productivity and ease in monitoring the plant growth process. Based on this, then in this study developed a data monitoring system that utilizes wireless multisensor network technology and internet connectivity in the concept of the Internet of Things (IoT). Through this system, it is expected to facilitate the process of monitoring and controlling the growth of plants that are turned into commodities.